1985
DOI: 10.1002/bip.360240605
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the α‐helical undecapeptide Boc‐L‐Ala‐Aib‐Ala‐Aib‐Ala‐Glu(OBzl)‐Ala‐Aib‐Ala‐Aib‐Ala‐OMe

Abstract: SynopsisThe x-ray structure of Boc-~-Ala-Aib-Ala-Aib-Ala-Glu(OBzl)-Ala-Aib-Ala-Aib-AlaOMe(1) represents the first a-helix determined by direct methods. This undecapeptide is a model of the N-terminus of alamethicin, and it exhibits voltage-dependent pores in bilayer membranes a t a higher voltage and concentration than alamethicin. The molecule crystallizes in the monoclinic space group P2, with a = 10.602(1), b = 23.884(3), c = 13.622(1) A, p = 95.61(6)", and 2 = 2. It adopts a right-handed a-helical conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 31 publications
(10 reference statements)
0
25
1
Order By: Relevance
“…The columns of head-to-tail-bonded helices must necessarily pack in a parallel fashion. This parallel packing of the a-helices is in contrast to the antiparallel packing generally observed in proteins and in other small a-helical structures (9)(10)(11).…”
contrasting
confidence: 82%
See 2 more Smart Citations
“…The columns of head-to-tail-bonded helices must necessarily pack in a parallel fashion. This parallel packing of the a-helices is in contrast to the antiparallel packing generally observed in proteins and in other small a-helical structures (9)(10)(11).…”
contrasting
confidence: 82%
“…The closest contacts between molecules in the lateral direction are 0(10). C(1) = 3.28 A and Cpl (9)...N(1) = 3.91 A near the bottom of one molecule and C81(2) ..C82(8) = 3.89 A near the top of the same molecule. All the other nearest approaches in the lateral directions are greater than 4.1 A.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Helical peptides (with more than 6 residues) in crystals have almost always been observed to pack in a head-to-tail motif that results in forming long rods or columns of helices throughout the crystal (Bosch et al, 1985a(Bosch et al, , 1985bFrancis et al, 1985;Marshall et al, 1990). In crystals where the succeeding a-helices in a column are in good register with respect to each other, 3 intermolecular NH.…”
Section: Head-to-tail Hydrogen Bondingmentioning
confidence: 99%
“…More recently, by theoretical (7)(8)(9)(10)(11) as well as experimental (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) investigations, it has been shown that the 4,q, angles ofthe achiral a-aminoisobutyric acid residue (Aib), the prototype of Caa-dialkylated a-amino acids, are restricted to values near those associated either with right-or left-handed a-or 310-helices, unless it is part of a strained cyclic compound (28). The x-ray diffraction structures of aaminoisobutyric acid homopeptides to the pentamer have provided examples of short (less than two complete turns) 310-helical conformations in the solid state (14,15,22,23).…”
mentioning
confidence: 99%